John Skelton: the Laureate of the People (Journal of the College of Basic Education, 2022)
The purpose of this paper is to shed light on the poetry of John Skelton in an attempt to identify his political orientation. Skelton spent many years of his life in the court of Henry VII and his son Henry VIII, but he did not write any poem that glorifies any of them. His true affiliation, it seems, was to the English people and the church which he tried to protect through his poetry as he felt that they are under the control of an unjust person called Cardinal Wolsey.